Estimating the period prevalence of non‐convulsive status epilepticus among comatose adults at the University Teaching Hospital in Lusaka, Zambia. Issue 4 (10th September 2019) - Buback, Clayton T.; Siddiqi, Omar K.; Titima, Innocent; Selioutski, Olga; Birbeck, Gretchen L.
Abstract: Objective: In Western settings, non‐convulsive status epilepticus (NCSE) and non‐convulsive seizures (NCSz) are associated with high mortality. In comatose patients, interictal epileptiform discharges (IEDs) identified on routine electroencephalogram (EEG) are predictive of NCSE/NCS. Little is known regarding the prevalence, causes, or outcomes of NCSE/NCSz in sub‐Saharan Africa (SSA). We sought to investigate the prevalence of IEDs and NCSE/NCSz at a single teaching institution in SSA. Methods: From October 3, 2017, to May 21, 2018, adult inpatients on the internal medicine service at Zambia's University Teaching Hospital (UTH) with a Glasgow Coma Score (GCS) of ≤10 were identified, excluding patients with mechanical ventilation or open head wounds. Signed consent by a proxy was required for enrollment and 30‐minute EEG. Chart abstractions provided coma duration, presence/absence of clinical seizures during/prior to admission, history of epilepsy, and presumed coma etiology. A structured neurological examination was completed. Patients were followed to discharge or death. Risk factors for IEDs were evaluated. Results: Of 392 eligible patients, 250 had EEGs. EEGs were not completed on eligible patients due to death (74), improved GCS (37), transfer within UTH (25), or lack of proxy (6). NCSE occurred in 22 of 250 (8.8%), NCSz in 3 of 250 (1.2%), and IEDs in 46 of 250 (18.4%) patients. Of the 250, 197 (78.8%) died. No specific risk factors for IEDs were identified. Significance: If the association between IEDs and NCSE among monitored populations in developed settings holds true for SSA, a projected 17%‐21% of comatose African adults have NCSE. No clinical characteristics identified those at risk.